Scorsese and Religion - Barnett, Christopher B.; Elliston, Clark J. (Studies in Religion and the Arts, 2019)
Scorsese and Religion explores and analyzes the religious vision of filmmaker Martin Scorsese's oeuvre, showing that Scorsese cannot be properly understood without reflecting on the ways that his religious interests are expressed in and through his art.; Readership: This book will appeal to scholars, students, and non-specialist readers interested in film's relation to philosophy, theology, and Christian spirituality.